CHI '10 Extended Abstracts on Human Factors in Computing Systems 2010
DOI: 10.1145/1753846.1753982
|View full text |Cite
|
Sign up to set email alerts
|

Touch your way

Abstract: Ji-Won Songand Graduate school of Techno Design, Kookmin University.Haptic Sight is a new interface idea providing immediate spatial information to visually impaired people in order to assist independent walking. The interface idea stems from a thorough investigation in which we studied visually impaired people's indoor walking behavior, decision making process, their unique concept of space, and information needs. The aim of this study is to identify an interface design and investigate an appropriate means of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 3 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…Independent use of technology is often a driving factor for the design of technology for people with disabilities [13,25,60]. Future interactions described by our participants build on the idea of independence described by Kameswaran et al [30].…”
Section: Future Interactionsmentioning
confidence: 87%
“…Independent use of technology is often a driving factor for the design of technology for people with disabilities [13,25,60]. Future interactions described by our participants build on the idea of independence described by Kameswaran et al [30].…”
Section: Future Interactionsmentioning
confidence: 87%
“…Studies on the navigational experiences of people with little to no functional vision (e.g. Banovic et al, 2013;Williams et al, 2014) found that blind pedestrians need to be aware of their physical location, their relation to the surrounding environment, and the route they must follow in order to be able to navigate to a desired destination (Song and Yang, 2010). Researchers have also addressed the use of technology as a means for enabling blind pedestrians to identify their location and orientation and successfully navigate in their surroundings (Fernandes et al, 2017).…”
Section: Assistive Technologies For Blind Pedestriansmentioning
confidence: 99%